Successful treatment of prolonged COVID-19 with remdesivir and nirmatrelvir/ritonavir in a patient with a history of diffuse large B-cell lymphoma: a case report - Nadia Bouhamdani; Dominique Bouhamdani; Cynthia Léger; Josiane Stadler; Nancy Saulnier (Journal of the Egyptian National Cancer Institute)
Abstract Background Immunocompromised individuals, such as those affected by and treated for hematological malignancies, face a higher risk of prolonged SARS-CoV-2 infection. Increased disease risk is further compounded by limited treatment options. Currently, approved antiviral monotherapies against COVID-19 include remdesivir (Veklury) and nirmatrelvir/ritonavir (Paxlovid) which have stringent recommended prescribing windows within 7 and 5 days of symptom onset, respectively. Furthermore, these two antiviral therapies are approved for treatment lengths of 3 (remdesivir) and 5 days (Paxlovid). Case presentation Herein, we describe the successful treatment of prolonged COVID-19 in a patient with a history of diffuse large B-cell lymphoma with an extended combination therapy; remdesivir and nirmatrelvir/ritonavir. The patient presented with symptomatic COVID-19 that was unsuccessfully treated with a 10-day course of remdesivir. After 2 months of symptomatic infection, the patient was treated with remdesivir in combination with nirmatrelvir/ritonavir for 10 days, which quickly resolved the cough and cleared viral load. Conclusion Our case highlights the efficacy of administrating a combination treatment of remdesivir and nirmatrelvir/ritonavir outside recommended guidelines for the treatment of persistent COVID-19 infection in an immunocompromised individual. High-quality studies evaluating the usefulness of this combinatory therapy as a longer-course treatment in patients with neoplasms is warranted.